TRAGIC MODEL OF THE WORLD IN CULTURAL INTERPRETATION PERSONALITIES IN THE LYRICS OF SIXTY POETS IN UKRAINIAN LITERATURE OF THE XX CENTURY (Pedagogy of Higher and Secondary Education, 2003)
No abstract.